The Terowongan Barang Bekas: A 2D RPG Game Designed Using RPG Maker MV - Windiarti, Ika Safitri; Ramadhan, Haris Hiqqal; Qamaruzzaman, Mohammad Haris (Jurnal Teknik, 2024)
"Terowongan Barang Bekas" is a 2D RPG game developed using RPG Maker MV, featuring a deep adventure within a mysterious tunnel filled with discarded items. The game utilizes the strong character customization features of RPG Maker MV, allowing players to create their main characters and interact with various supporting characters throughout the storyline. The gameplay revolves around puzzle-solving, overcoming challenges, and engaging in strategic battles. Players will encounter intriguing puzzles that require their intelligence and problem-solving skills to progress. The battle system offers a balance between strategy and action, where players must utilize their character's abilities, strengths, and weaknesses to emerge as the winner. With carefully selected audio elements such as music, background sounds, and immersive sound effects, "Terowongan Barang Bekas" creates an atmospheric experience that enhances the gameplay and brings the game world to life. The game development process emphasizes comprehensive testing and bug fixes to ensure a smooth and enjoyable gaming experience.